Analisis Penerapan Metode Pencatatan dan Penilaian Persediaan Barang Dagang Berdasarkan PSAK Nomor 14 Pada CV. Irama Plastindo - Jessica Violita Hadi; Tries Ellia Sandari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research applies descriptive research using a qualitative approach. This research uses primary data and secondary data with data collection techniques applying interview and documentation techniques. The aim of the research to be achieved is to determine the application of the method of recording and assessing merchandise inventory carried out by CV. Irama Plastindo and knowing the suitability of applying recording and assessment methods at CV. Irama Plastindo with PSAK Number 14 in effect. Based on the results of research conducted, CV. Irama Plastindo has not yet fully implemented the recording and assessment method for inventory calculations with PSAK Number 14. However, occasionally this business entity implements a stock taking system, because demand and stock are more in demand.